2012
DOI: 10.5603/20321
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression and distribution of orexin, orphanin and leptin in the major salivary glands of some mammals

Abstract: The aim of the study was to determine by immunochemistry the expression of leptin, orexin A and orphanin FQ in the major salivary glands (parotid, submandibular and sublingual) of rat, sheep and cow. These peptides, originally synthesized in central nervous system, adipose tissue and peripheral tissues including gastrointestinal tract, play an orexigenic (orphanin and orexin) or anorexigenic (leptin) roles in the intricate neuronal network appointed to the control of nutritional homeostasis. Peptide-specific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Similar to previous research, it was determined that the peptide hormones investigated in the present study were expressed at varying intensity in the luminal epithelial and glandular and ductal epithelial cells of the sheep tongue (Leone et al, ). In agreement with the reports of Alnema et al () and Ohta et al () for human oral epithelial cells, the present study demonstrated moderate ghrelin, obestatin and leptin expression in the luminal epithelial cells of the sheep tongue.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Similar to previous research, it was determined that the peptide hormones investigated in the present study were expressed at varying intensity in the luminal epithelial and glandular and ductal epithelial cells of the sheep tongue (Leone et al, ). In agreement with the reports of Alnema et al () and Ohta et al () for human oral epithelial cells, the present study demonstrated moderate ghrelin, obestatin and leptin expression in the luminal epithelial cells of the sheep tongue.…”
Section: Discussionsupporting
confidence: 85%
“…Feeding mechanisms are an important factor that defines the success of the environmental adaptation of vertebrates (Roth & Wake, ). It is well known that food digestion starts in the mouth under the control of the secretion of the major and minor glands localized to the mucosa of the oral cavity and the oropharyngeal organs (Leone et al, ). The results of the present study demonstrated that, in sheep, the tongue, which has a vital role in nutrition together with other organs of the digestive system (i.e., the stomach and intestines), is also a source of the peptide hormones leptin, ghrelin and obestatin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations